A post-hoc analysis of risk factors for poor quality of life after surgical treatment of spondylodiscitis - Krishnan Sircar; Dorothee Jochimsen; Charlotte Meyer-Schwickerath; Norma Jung; Nikolaus Kernich; Peer Eysel; Ayla Yagdiran (Scientific Reports)
Abstract Patient-reported outcome measures for quality of life (QoL) like the Oswestry-Disability-Index (ODI) are useful for a quick, comprehensive and comparable evaluation of spondylodiscitis treatment. While it is known that even after successful surgical treatment, the QoL of spondylodiscitis patients remains below that of the general population, risk factors for a poor outcome have not been described so far. We did a retrospective post-hoc analysis of 130 surgically treated spondylodiscitis patients from 2008 to 2022. Biographical, clinical und QoL data were prospectively collected before (T0) and one year (T1) after surgery. The primary outcome was QoL at T1. Patients were grouped according to their ODI score at T1 (Group 1: ODI < 35, favorable QoL; Group 2: ODI ≥ 35, poor QoL) and analyzed for risk factors present at T0. Poor QoL at T1 occurred in 51 patients (39%). Multivariate analysis identified a higher preoperative leg pain (odds ratio: 1.2) and the presence of a malignant disease (odds ratio: 1.9) as independent preoperative risk factors for a poor QoL at T1. Spondylodiscitis patients with malignancy and/or preoperative leg pain may be at increased risk for poor QoL after surgical treatment. These results can be used to individualize patient information and provide a better assessment of prognosis before surgery.